دراسة أولية للتغير الفصلي لبعض خصائص التربة ومياه الصرف الزراعي في منطقة شطحة – سهل الغاب - الجردي, أحمد; ترت, محمد (Latakia University Journal -Biological Sciences Series, 2019)
أظهرت النتائج التي أجريت على التربة في منطقة شطحة من سهل الغاب وللأعماق (0 - 20) و (20 - 30) و (30 - 56 سم) خلال الفصول الأربعة، وعلى مياه الصرف الزراعي الراشحة شهرياً ولفترة سنة كاملة الآتي: - كان قوام التربة لومي إلى لومي طيني في الأعماق (0-20) – (20-30) و (30 – 56 سم)، دليل وجود الأفق التراكمي - ارتفعت قيم الكثافة الظاهرية للطبقة السطحية خاصة في فصل الشتاء، وانخفضت في فصل الصيف. - لم تتجاوز المسامية الكلية 46 % بسبب ارتفاع قيم الكثافة الظاهرية وانخفاض الكثافة الحقيقية. - كانت التربة حامضية (5.5 pH)، وكان محتوى التربة من الألمنيوم الذائب مرتفعا إذ تراوح ما بين (11.10- 18.01) مغ / لتر، وانخفضت نسبة التشبع بالقواعد ما بين (57.52 – 66.53) / في 100 غ تربة - تميزت مياه الصرف الزراعي بسيادة تركيز انيونات البيكربونات والكلور والكبريتات وكاتيونات الكالسيوم والمغنيزيوم والبوتاسيوم في فصول الشتاء والخريف والربيع. The tests made on the soil in the region of Shatha-Alghab plain, in depths of (0-20 cm) and (20-30 cm) and (30-56 cm) during the four seasons, and on the agricultural drainage water monthly and for a complete year, have given the following results: - The texture of soil has been Loamy to clay in the depths 30-56 cm. - The bulk density of the surface layer has risen particularly in winter season and lower in summer season. - The total porosity has not exceeded 46% due to the rise in the bulk density values and lower of the real density. - Soil acidity degree was (5.5 pH), and the rate of the organic substance was low. But the rate of the solved aluminum content was high (11.10-18.01mg/l), where the rate of saturated soil in alkaline ranged between 57.52 and 66.53/100 g of soil. From the predominant anions were the bicarbonate and chlorine in winter, autumn and spring, and from the cations were the calcium and magnesium.